Reducing tunnel vision with a pen‐and‐paper tool for the weighting of criminal evidence. Issue 2 (14th April 2018) - Rassin, Eric
Abstract: In order to prevent tunnel vision, and ultimately miscarriages of justice, police, prosecutors, and judges must remain open to alternative scenarios in which the suspect is in fact innocent. However, it is not evident from the literature that people are sufficiently aware of how alternative scenarios should be employed in the decision‐making process. In the present research, participants read a case vignette and formed an impression of the suspect's guilt. Some participants were made familiar with an alternative scenario. Others were not only presented with an alternative scenario but were also instructed to score (with pen and paper) the extent to which every piece of evidence fitted in the primary and the alternative scenario. Findings suggest that this pen‐and‐paper task helped to reduce tunnel vision.